Red pigment and citrinin formation by a local isolate of Monascus sp. - Cereno, Celia A.
Monascus is a known source of natural pigments. It has been reported to produce other economically important secondary metabolites but it was recently discovered to produce citrinin, a nephrotoxic and hepatoxic compound. Monascus sp. UPCC 3765, a local isolate from the Culture Collection of the UP-Natural Sciences Research Institute, was tested for the production of water-soluble red pigments and citrinin in shake-flask culture on eight variations of chemically-defined media with either glucose or sucrose as carbon source. UPCC 3765 was found to better utilize sucrose than glucose for pigment synthesis in the basic media with OD490 of 6.145 and 3.068, respectively. Sucrose also produced twice as much citrinin as glucose at 8.20 ppm and 4.44 ppm, respectively. The supplementation of the basic media with acetate, pyridoxamine or a combination of pyridoxamine and octanoate exhibited different effects on the pigment and citrinin production by UPCC 3765. Of the eight culture media tested, three exceeded OD 490 6.0: glucose with pyridoxamine (7.358), glucose with acetate (6.941) and basic sucrose (6.145). The three supplemented sucrose media, basic glucose and glucose with pyridoxamine and octanoate yielded less than OD490 4.0. Results indicate glucose with acetate to be the best medium with the red pigment and citrinin at OD490 6.941 and 4.95 ppm, respectively. Basic sucrose follows with OD490 6.145 and 8.20 ppm citrinin. Glucose with pyridoxamine promoted the highest pigment production(OD490 7.358) but it had extremely high citrinin (60.93 ppm).